Exploring provider's perceptions on the facilitators and barries to implementation of nurse intiated management antiretroviral therapy in Manzini region, Swaziland - Ngwarati, Innocent (My University, 2015)
Introduction: Swaziland is facing a very high HIV prevalence and critical human resources for health (HRH) crisis. The Nurse Initiated and Managed Anti-Retroviral Treatment (NIMART), a task shifting program to capacitate nurses to offer ART services, was introduced in 2009 by the government of Swaziland to address the human resources for health (HRH) challenges in the country. Although the country has attained 80% coverage in ART provision amongst adults, the ART coverage in children below 15 years of age is 9% which falls way below the WHO stipulated proportion of 15% in that age group. In addition, ever since the NIMART was introduced there have been limited studies done in Swaziland to explore the perceptions of health workers with regards to its implementation. This study explored providers’ perceptions on the facilitators and barriers to the NIMART implementation in Manzini Region. Materials and Methods: An exploratory qualitative study was used to explore providers’ perceptions of the facilitators and barriers to the implementation of NIMART services in Manzini Region, Swaziland. A semi-structured interview guide was used to interviews with nurses, clinic managers and medical doctors who were purposively selected from five urban and three rural clinics offering NIMART services in Manzini Region, Swaziland. Thematic content analysis was used to analyse data guided by the Donabedian conceptual framework. Results: The findings showed that two weeks training was offered to the professional nurses before they were certified as NIMART nurses. The first week of training was mainly theory classes while the second week was on-site practical training. The NIMART program was perceived as vital by the providers interviewed as it improved access to ART, reduced patient waiting times, empowered nurses and was a cost effective program to address the shortages of doctors in the country. Structural factors like availability of health facilities, professional nurses, antiretroviral drugs and antiretroviral treatment guidelines at the facilities visited were reported by most respondents as facilitators of the implementation of the program. Process factors like the training of NIMART nurses in some facilities, the partnership between the Ministry of Health and various nongovernmental organisations, the health workers commitment and team work greatly facilitated NIMART implementation. Structural barriers like limited paediatric antiretroviral regimen choices and limitations in paediatric ART policy and legislation were mentioned to negatively affect ART uptake in children. Other barriers like children’s dependency on adult caregivers for their health issues and poor socioeconomic circumstances in communities were mentioned to be hampering ART uptake in children. Process factors like inadequate training of the NIMART nurses in some clinics, parents’ and caregivers’ myths and misconceptions around HIV, AIDS and ART, high HIV and AIDS stigma and poor access to health services were also raised. Conclusion and Recommendations: Even though there were facilitating factors of the NIMART program like availability of ART drugs and ART treatment guidelines which have been seen to have played a major role in ART uptake in adults, there are still many barriers to the implementation of NIMART as evidenced by the poor ART uptake in children. The inadequate training of NIMART nurses on paediatric ART, children’s total dependency on adults for their health needs and parents’ and caregivers’ misconceptions around HIV and AIDS negatively impacted the paediatric ART program. Other barriers included poor socioeconomic status and paediatric ART policy and legislation limitations. As a result, the recommendations are that the NIMART training program for nurses be improved with particular emphasis on paediatric ART. There is need to incorporate NIMART training into the nursing curriculum to ensure that more nurses are trained in ART provision. Community awareness needs be raised to address the issues around stigma, myths and misconceptions of HIV and AIDS through educational programs. There is also a need to increase the recruitment of nurses and improve motivation of nurses through provision of incentives.
Research report submitted in fulfilment of the degree of Master of Public Health (MPH) at the University of Witwatersrand July 2015
Keywords: Antiretroviral Therapy, Highly Active; HIV